CONCEPT ANALYSIS AND FINANCIAL PERFORMANCE IN CONVENTIONAL AND ISLAMIC BANKS ON PERIODE 2016-2020 (JEM17: Jurnal Ekonomi Manajemen, 2022)
Banking is one of the essential elements of economic sustainability. Indonesia has two banking systems: banking with conventional principles and banking with sharia principles. Differences in the regulation of the system can affect the results of the bank's performance. So, it is necessary to analyze the comparison of bank performance to determine the significance of the differences. This research aims to present the findings of a financial performance analysis carried out on Islamic and conventional banks' financial statements in 2016-2020. This study analyzes by looking at financial performance ratios consisting of Capital Adequacy Ratio (CAR), Return on Assets (ROA), Return on Equity (ROE), Operating Costs, and Operating Income (BOPO), and Financing Deposit Ratio (FDR). ) using SPSS. 36. The results obtained are significant differences between CAR, ROA, ROE, BOPO, and FDR of conventional and Islamic banks. Islamic banks' CAR, ROE, BOPO, and FDR values are better than conventional banks, while conventional banks' ROA is better than Islamic banks. Keywords: Conventional Banks, Financial Performance, Islamic Banks